Airway Assessment in Patients Undergoing Surgery and General Anaesthesia and its Application in Prediction of Difficult Airway - Nandita Kad; Mangal Ahlawat; Nikita Bajaj; Priyanka Bansal (International Journal of Scientific Research in Dental and Medical Sciences)
Background and aim: Anaesthesiologists face challenges in airway management, but pre-anesthetic airway assessment helps identify potential complications and prepare alternative plans for children with challenging airways. The primary goal of airway assessment during pre-anesthetic evaluation is to identify difficult airways and prepare alternative treatments for mask ventilation, direct laryngoscopy, and endotracheal intubation. Material and methods: Patients aged 8-14 years, of either sex, with an American Society of Anesthesiologists (ASA) grade I or II, were included. Four parameters, namely the modified Mallampati test, neck circumference, measurement of thyromental distance, and the Ratio of height to thyromental distance, were assessed pre-operatively using the same flexible measuring tape to avoid instrumental bias. These parameters were then correlated with Cormack and Lehane's grading system for assessing a difficult airway. Results: All four parameters, namely modified Mallampati test, thyromental distance, Ratio of height to thyromental distance, and neck circumference, were found to be statistically significant in predicting difficult airway in children of the age group 8-14 years. Out of the four parameters assessed, the Ratio of Height to Thyromental Distance (RHTMD) had the highest sensitivity of 98.41%, followed by Mallampati grading (MPG) with a sensitivity of 96.83%, suggesting that they are highly sensitive predictors of difficult airways in children. Conclusions: To predict airway status in children, the modified Mallampati test is the most useful parameter, which can be used as a bedside screening test in the 8-14 year age group, as it has high sensitivity and the highest diagnostic accuracy.